2017
DOI: 10.1136/bmjspcare-2016-001146
|View full text |Cite
|
Sign up to set email alerts
|

Key issues affecting quality of life and patient-reported outcomes in prostate cancer: an analysis conducted in 2128 patients with initial psychometric assessment of the prostate cancer symptom scale (PCSS)

Abstract: Objective Evidence-based quality of life (QL) questionnaires require the identification of issues of importance to patients. The primary aim of this study was to inform providers on patient-expressed issues while enhancing the content validity of instruments assessing quality of life (QL) and patient reported outcomes (PROs) in prostate cancer. The study provided additional psychometric properties for the new PRO and QL instrument, the Prostate Cancer Symptom Scale (PCSS). Methods An anonymous web-based surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…It is now recognized that cancer has a physical and mental impact not only on the individuals diagnosed [ 2 ], but also on those who provide them with support—their family caregivers [ 15 , 18 ]. With this recognition, an increasing number of patient–caregiver interventions (or dyadic interventions) have been developed [ 20 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now recognized that cancer has a physical and mental impact not only on the individuals diagnosed [ 2 ], but also on those who provide them with support—their family caregivers [ 15 , 18 ]. With this recognition, an increasing number of patient–caregiver interventions (or dyadic interventions) have been developed [ 20 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer is the most common cancer among men [ 1 ]. Despite increasing survival rates, prostate cancer and its treatment remain a major life stressor [ 2 , 3 ], and confront men with many physical symptoms (e.g., urinary incontinence, bowel dysfunction, and sexual dysfunction) [ 4 , 5 ] and psychosocial challenges (e.g., anxiety, depression, and fatigue) [ 6 , 7 , 8 ]. These challenges often remain poorly managed, resulting in impaired functioning and lower quality of life than the general population [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining QoL and current lifestyle without compromising physical wellbeing are important considerations to patients with nmCRPC 29 . Given that TEAEs can negatively impact QoL, treatment compliance and outcomes, and are associated with increased healthcare utilization and cost, therapeutic benefit must always be balanced against the potential risk of AEs 20 .…”
Section: Tailoring Treatment To Patientsmentioning
confidence: 99%
“…The disease progression of PC is often slow and the life expectancy at all stages has increased considerably due to new and improved treatments (Siegel et al, 2018). Quality of life (QoL) is very important for men with PC at all stages of the disease (Msaouel et al, 2017). A study comparing patient-reported outcomes between men with local disease (tumor stages 1-2) and men with tumor stages 3 and 4 found that even though the group with more advanced cancer reported more problems with fatigue and hormonal function (due to hormone treatment), health-related QoL (HRQoL) did not differ substantially between the groups (Downing et al, 2019).…”
Section: Introductionmentioning
confidence: 99%